Effects of Metoprolol on Periprocedural Myocardial Infarction After Percutaneous Coronary Intervention (Type 4a MI): An Inverse Probability of Treatment Weighting Analysis - Li, Duanbin; Li, Ya; Lin, Maoning; Zhang, Wenjuan; Fu, Guosheng; Chen, Zhaoyang; Jin, Chongying; Zhang, Wenbin (Frontiers in Cardiovascular Medicine, 2021)
Background Metoprolol, the most used cardiac selective β-blocker, has been recommended as a mainstay drug in the management of acute myocardial infarction (AMI). However, the evidence supporting this strategy in periprocedural myocardial infarction (PMI) is limited. Methods This study identified 860 individuals who suffered PMI following percutaneous coronary intervention (PCI) procedure and median followed up for 3.2 years. Subjects were dichotomized according to whether they received chronic oral sustained-release metoprolol succinate following PMI. After inverse probability of treatment weighting (IPTW) adjustment, logistic regression analysis, Kaplan-Meier curve, and Cox regression analysis were performed to estimate the effects of metoprolol on major adverse cardiovascular events (MACEs), composed of cardiac death, myocardial infarction (MI), stroke, and revascularization. Besides, exploratory analysis was performed according to hypertension, cardiac troponin I (cTnI) elevation, and cardiac function. A double robust adjustment was used for sensitivity analysis. Results Overall, 456 (53.0%) patients diagnosed with PMI after PCI received metoprolol treatment, and 404 (47.0%) patients received observation. After IPTW adjustment, receiving metoprolol was observed to reduce the subsequent 3-year risk of MACEs by nearly 7.1% [15.0% vs. 22.1%, absolute risk difference (ARD)=0.070, number needed to treat (NNT)=14, relative risk (RR)=0.682]. In IPTW-adjusted Cox regression analyses, receiving metoprolol was related to a reduced risk of MACEs (HR=0.588, 95%CI [0.385 to 0.898], P=0.014) and revascularization (HR=0.538, 95%CI [0.326 to 0.890], P=0.016). Additionally, IPTW-adjusted logistic regression analysis showed that receiving metoprolol reduced the risk of MI at the 3rd year (OR=0.972, 95% CI [0.948 to 0.997], P=0.029). Exploratory analysis showed that the protective effect of metoprolol was more pronounced in subgroups of hypertension and cTnI elevation ≥ 1000%, and was remained in patients without cardiac dysfunction. The benefits above were consistent when double robust adjustments were performed. Conclusion In the real-world setting, receiving metoprolol treatment following PCI-related PMI decreased the subsequent risk of MACEs, particularly the risk of recurrent MI and revascularization.